2015
DOI: 10.1021/acs.organomet.5b00488
|View full text |Cite
|
Sign up to set email alerts
|

Facile Aerobic Alkylation of Rhodium Porphyrins with Alkyl Halides

Abstract: Alkylation of rhodium porphyrins was achieved in moderate to high yields in the presence of air and water. With this facile alkylation method, various alkyl Rh III (por) species, including those with tertiary alkyl, were synthesized. Mechanistic investigations suggest a parallel S N 2 via [Rh I (ttp)] − with halogen atom transfer pathway via [Rh II (ttp)] • . ■ INTRODUCTIONRhodium porphyrin alkyls ( Figure 1) play an important role in catalysis. They are precursors of [Rh II (por)] • (por = porphyrinato dianio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Based on our previously reported mechanism on the base-promoted cleavage of aryl halides with Ir(ttp)(CO)Cl (1) 16,17 and recently reported base-promoted alkylation of rhodium porphyrins, 25 1). [Ir I (ttp)] − is likely more air compatible since it is a weak base.…”
Section: Mechanistic Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previously reported mechanism on the base-promoted cleavage of aryl halides with Ir(ttp)(CO)Cl (1) 16,17 and recently reported base-promoted alkylation of rhodium porphyrins, 25 1). [Ir I (ttp)] − is likely more air compatible since it is a weak base.…”
Section: Mechanistic Discussionmentioning
confidence: 99%
“…It is in contrast with the occurrence of some extent of halogen atom transfer for the rhodium porphyrin analogues with a weaker Rh-Rh bond (∼16 kcal mol −1 ). 25,29,30 For 3°alkyl halides, it undergoes base-promoted elimination by hydrodehalogenation to give an alkene like that of t BuCl. For 1-bromoadamantane, this elimination gives a bridge-headed olefin which is highly unfavorable.…”
Section: Mechanistic Discussionmentioning
confidence: 99%
“…Previous studies by our group and others have shown that rhodium­(III) porphyrin complexes, Rh III (por)­X (por = porphyrinato dianions; X = H, alkyl, acyl, halides, Figure ), can mediate various stoichiometric bond activations of different organic functional groups. Reported examples include (i) carbon–carbon bond activation (CCA) with hydrocarbons, ketones, ethers, , amides, esters, nitriles, , and nitroxides; , (ii) carbon–hydrogen bond activation (CHA) with alkanes, toluenes, ,, alcohols, aldehydes, , and ketones; (iii) carbon-halogen bond activation (CXA) with alkyl halides and aryl halides; (iv) carbon–oxygen bond activation (COA) with alcohols , and ethers; (v) carbon–nitrogen bond activation (CNA) with amines; and (vi) silicon–hydrogen bond activation with silanes . However, to the best of our knowledge, the reactivity of Rh III (por)­X toward carboxylic acids has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has communicated the alkylation of Rh III (ttp)Cl with alkyl halides under basic conditions. 7 Both the Rh II (ttp) metalloradical and Rh I (ttp) − anion generated in situ from Rh III (ttp)Cl are responsible for cleaving the alkyl R−X bond (X = Cl, Br, I) by halogen atom abstraction and nucleophilic substitution, respectively (Scheme 1c). This alkylation protocol gives access to Rh III (ttp)R with 1°, 2°, and even 3°alkyl ligands in air.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This air-tolerant transformation also takes advantage of the nucleophilicity of the Rh I (tpp) − anion generated in situ under basic conditions. Our group has communicated the alkylation of Rh III (ttp)Cl with alkyl halides under basic conditions . Both the Rh II (ttp) metalloradical and Rh I (ttp) − anion generated in situ from Rh III (ttp)Cl are responsible for cleaving the alkyl R–X bond (X = Cl, Br, I) by halogen atom abstraction and nucleophilic substitution, respectively (Scheme c).…”
Section: Introductionmentioning
confidence: 99%